Factors Affecting Infectious Endocarditis, Clinical Manifestation and Treatment Modalities – A Nurse's perspective and Overview: Life Sciences-Medicine - . M, Malarmathi; lakshmi, Raja; N, Dhivya; .M, Meena (International Journal of Life Science and Pharma Research, 2023)
Infectious endocarditis virulent microorganisms colonize the endocardium heart valve. It is a rare disorder, and if it is not adequately recognized and treated, it can cause severe and quick morbidity and mortality; as per incidence in the US, approximately 10,000 to 15,000 are affected by infectious endocarditis. Nurses are critical in the prevention, early detection, early diagnosis workup, and prompt, successful care of this deadly disease and its complications. This article provides a review and updates on this striking yet ambiguous disease. Nurses will be effectively able to plan, incorporate, and evaluate the care required by this distinctive and demanding patient population if existing understanding is transferred into practice. Monitoring vitals like pulse, blood pressure, and temperature and alerting the physician significantly decreases morbidity. Administration of appropriate antibiotics at the proper doses and timing also matters. They also need to monitor the patient's renal status, including blood urea nitrogen levels, creatinine clearance levels, and urine output, especially a sudden appearance of blood in the urine. A Simple look at the nail beds for cyanosis is not a complete replacement for pulse oximetry but remains valid. As far as taking specimens for investigations, precise knowledge is needed. Using vacuum-extracted blood collection systems when we contemplate culture specimens is preferable. A complete education about possible infection sources and cleanliness, like decayed teeth, should be explained to patients. All plastics inside, like intravenous access and urinary catheter, should be treated with complete asepsis. As the disease is sudden, a calm, soothing approach towards patients and attendees goes a long way in getting better outcomes for these patients.